Thermodynamic Speed of Sound Data for Liquid and Supercritical Alcohols - Javed, Muhammad Ali; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Thermodynamic speed of sound of xenon - Javed, Muhammad Ali; Baumhögger, Elmar; Vrabec, Jadran (The Journal of Chemical Thermodynamics)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (Chemical Engineering Transactions)

Numerical Investigation of the Temperature Distribution in PCM-integrated Solar Modules - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny (CHEMICAL ENGINEERING TRANSACTIONS)

Numerische Untersuchung der Temperaturverteilung in PCM-integrierten Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Kenig, Eugeny

Entwicklung eines thermischen 1D-Simulationsmodells zur Bestimmung der Temperaturverteilung in Solarmodulen - Grabo, Matti; Weber, Daniel; Paul, Andreas; Klaus, Tobias; Bermpohl, Wolfgang; Krauter, Stefan; Kenig, Eugeny

Bestimmung von Wärmeverlusten in Haushaltskältegeräten - Paul, Andreas; Moczarski, Lukas; Gieselmann, Mirko; Reineke, Michael; Elsner, Andreas; Baumhögger, Elmar; Sonnenrein, Gerrit; Vrabec, Jadran
Wie jedes technische System unterliegen auch Haushaltskältegeräte einer alterungsbedingten Degeneration, die zu einem Anstieg der Energieaufnahme über die Lebensdauer dieser Geräte führt. Ursache hierfür sind verschiedene Effekte, die in dem vom BMWi geförderten Projekt ALGE untersucht werden. Aus den so gewonnenen Erkenntnissen sollen dann degenerationsbeständigere Haushaltskältegeräte entwickelt werden. Eine wichtige Alterungsursache ist der Anstieg der Wärmeleitfähigkeit des PUR-Schaums der Gehäuseisolierung. Zur Bestimmung dieses Einflusses auf die Energieaufnahme ist die Entwicklung neuer Messmethoden notwendig, die zerstörungsfrei sein und den realen Anwendungsbedingungen möglichst nahekommen sollen. Dazu wurde eine Wärmesenke entwickelt, die den Geräteinnenraum unabhängig vom Kältekreislauf abkühlt. Die Wärmesenke ist als Eiswasserbehälter ausgeführt, sodass die Schmelzenthalpie des Eises die durch die Isolierung in den Geräteinnenraum einfallende Wärme aufnimmt. Durch die Bestimmung der Abtauzeit einer bestimmten Eismenge kann so der alterungsbeeinflusste 𝑘∙𝐴-Wert des Gehäuses von Haushaltskältegeräten bestimmt werden.

Speed of Sound Measurements and a Fundamental Equation of State for Hydrogen Chloride - Thol, Monika; Dubberke, Frithjof H.; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Speed of Sound Measurements and a Fundamental Equation of State for Hydrogen Chloride - Thol, Monika; Dubberke, Frithjof H.; Baumhögger, Elmar; Span, Roland; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Large Scale Thermodynamic Data Generation with Molecular Simulation - Rutkai, Gábor

A Spectral Approach to Acoustic Absorption Measurement - Claes, Leander; Chatwell, René Spencer; Vrabec, Jadran; Henning, Bernd (PROCEEDINGS -- AMA Conferences 2017)

Experimental setup of a cascaded two-stage organic Rankine cycle - Dubberke, Frithjof H.; Linnemann, Matthias; Abbas, Wameedh Khider; Baumhögger, Elmar; Priebe, Klaus-Peter; Roedder, Maximilian; Neef, Matthias; Vrabec, Jadran (Applied Thermal Engineering)

Experimental and Computational Study on the Solubility of Argon in Propan-2-ol at High Temperatures - Nikolaychuk, Pavel Anatolyevich; Linnemann, Matthias; Muñoz-Muñoz, Y. Mauricio; Baumhögger, Elmar; Vrabec, Jadran (Chemistry Letters)

Thermophysical properties from experimental speed of sound measurements for working fluids in organic Rankine cycles - Dubberke, Frithjof

Molekulare Simulation als effizientes Werkzeug zur Bestimmung thermodynamischer Stoffdaten - Köster, Andreas

Modeling and simulation of metallic, particle-damped spheres for lightweight materials - Steinle, Tobias
Lightweight materials play an ever growing role in today's world. Saving on the mass of a machine will usually translate into a lower energy consumption. However, lightweight applications are prone to develop performance problems due to vibration induced by the operation of the machine. The Fraunhofer Institute for Manufacturing Technology and Advanced Materials in Dresden conducts research into the damping properties of composite materials. They are experimenting with hollow, particle filled spheres embedded in the lightweight material. Such a system is the technical motivation of this thesis. Ultimately, a numerical experiment to derive the coefficient of restitution is required. The simulation developed in this thesis is based on a discrete element method to track the individual particle and sphere trajectories. Based on a potential based approach for the particle interactions deployed in molecular dynamics, the behavior of the particles can be controlled effectively. The simulated volume is using reflecting boundaries and encloses the hollow sphere. In this work, a highly flexible memory structure was used with a linked cell approach to cope with the highly flexible mass of particles. This allows for a linear complexity of the method in regard to the particle number by reducing the computational overhead of the interaction computation. Multiple numerical experiments show the great effect the particles have on the damping behavior of the system.

Experimental study of phase change materials for photovoltaic modules: Energy performance and economic yield for the EPEX spot market - Japs, Ewald; Sonnenrein, Gerrit; Krauter, Stefan; Vrabec, Jadran (Solar Energy)

Speed of Sound of Oxygen in Supercritical States up to 500 K and 100 MPa - Dubberke, Frithjof H.; Riepold, Markus; Baumhögger, Elmar; Vrabec, Jadran (Journal of Chemical & Engineering Data)

Molecular modeling and simulation for industrial applications - Miroshnichenko, Svetlana

Copolymer-bound phase change materials for household refrigerating appliances: experimental investigation of power consumption, temperature distribution and demand side management potential - Sonnenrein, G.; Baumhögger, Elmar; Elsner, A.; Fieback, K.; Morbach, A.; Paul, A.; Vrabec, J. (International Journal of Refrigeration)